2014
DOI: 10.5194/sed-6-3333-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of soil fertility in the succession of karst rocky desertification using principal component analysis

Abstract: Abstract. Expanding of karst rocky desertification (RD) area in southwestern China has led to destructed ecosystem and local economic development lagging behind. It is important to understand the soil fertility at RD regions for the sustainable management of karst lands. The effects of the succession of RD on soil fertility were studied by investigating the stands and analyzing the soil samples with different RD grades in the central Hunan province, China, using the principal component analysis method. The res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Indicators of rangeland degradation provide information that should improve the understanding of complex phenomena such as desertification and ecosystem changes. The selection of relevant indicators is therefore a crucial step in providing measurable criteria for monitoring, managing and providing policy support on land degradation (Van Lynden et al ., ; Izzo et al ., ; Liu et al ., ; Xie et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Indicators of rangeland degradation provide information that should improve the understanding of complex phenomena such as desertification and ecosystem changes. The selection of relevant indicators is therefore a crucial step in providing measurable criteria for monitoring, managing and providing policy support on land degradation (Van Lynden et al ., ; Izzo et al ., ; Liu et al ., ; Xie et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The aggravation of RD is not only caused by anthropogenic factor (land overuse) , but also by climate change [19]. For all investigated stands, we found that degradation of phytocommunity (tree → tree/shrub → shrub → shrub/grass → grass) results in the homogenization of community structure, decrease of biomass and litter fall, and reduction of plant nutrition [8]. The destroyed soil ecosystem leads to soil microorganism population reducing and microbial activity on discomposing litter fall decreasing, so that the C, N, and P fixation of soil decreases [20].…”
Section: Discussionmentioning
confidence: 93%
“…Succession of RD refers to the changing process of karst land from one grade to another here and elsewhere [7], which means an observable process of changes of karst ecosystem such as vegetation type, vegetation coverage, bedrock exposure, and soil depth from potential RD to intensive RD orderly or vice versa [8]. In karst ecosystem, in order to find sensitive indicators to evaluate soil fertility, many researches discussed the interactions among vegetation, soil physical and chemical conditions, and soil microbial properties.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Millennium Ecosystem Assessment (MEA, 2005), 10-20% of the drylands are already moderately degraded. Desertification becomes one of the most important social, economic and environmental problems in the world today (da Silva Pinto Vieira et al, 2014;Xie et al, 2014;Easdale, 2015). Desertification has developed rapidly in oases of northern China over the last 50 years, which is a major obstacle to the sustainable development of oases (Wang et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%